Collecting and Sharing Observations with Semantic Support - Vainikainen, Sari; Nummiaho, Antti; Bäck, Asta; Laakko, Timo (Proceedings of the International AAAI Conference on Web and Social Media, 2009)
We present two applications that can be used to store and share ideas, bookmarks and observations from the web and on the move. These applications utilize semantic web technologies both to support users in tagging and to store and integrate data. The core of the system is a social bookmarking application, Tilkut, complemented with a mobile application TagIt, which can be used to send photo and text entries from a mobile device. Tag suggestions are given from external ontologies, and from earlier tags. TagIt stores its data in an RDF database, which is also used in integrating these applications. The ontology for the RDF database combines existing social media ontologies, and its key structures are presented. The paper shares our experiences from linking and using external ontologies, and its special challenges on mobile applications.